Evaluasi Kemandirian Belajar IPA Siswa - Ahmad Amin; Hadiwinarto Hadiwinarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to evaluate the independence of science learning for seventh-grade students of SMP Negeri 3 Lubuklinggau in the 2021/2022 academic year. The method used is descriptive quantitative. Data collection techniques in this study used interviews and questionnaire techniques. The learning independence understudy is independent with responsibility indicators, strong self-confidence and creative thinking. The results showed that students with learning independence in the medium category were five people (22%), students with very good learning independence were five people (22%) and students with learning independence in the good category were 13 people (56%). The average learning independence of grade VII.5 students of SMP Negeri 3 Lubuklinggau is in the good category with a score of 78. In conclusion, grade VII students of SMPN 3 Lubuklinggau have high learning independence in science subjects. Keywords: Evaluation, Independent Learning